Evaluación del tratamiento de semen bovino con anticuerpos específicos contra la Rinotraqueitis Infeccionsa Bovina -RIB- : ensayos preliminares (1996)
ABSTRACT: Because BHV-1 can be shed semen of infected bulls natural mating and artificial insemination represent a serious risk for massively infecting bovine herds. The focus of our attention in this report is the possibility of rescuing the genetic potential of BON bulls. Much of the good quality semen whose breed is at risk extinction belongs to BHV-1 infected bull. We reasoned that if the virus is extracellular in this fluid, it could be possible to Nt it with specific antibodies. As hen's yolk is routinely used for semen preservation, an attempt was made to produce BHV-1 antibodies in hens. To determine HBV-1 immunoglobulin's in hen serum and egg yolk competitive ELISA and serum neutralization tests were performed. It was not possible to detect an anti_BHV-1 antibody response in two bred of hens and with different inoculations protocols. Alternatively, a bovine serum with a Nt title of 32 was used to treat experimentally infected semen samples in conditions similar on for semen freezing, this treatment was able to completely neutralize 6.4 ID of the virus but only partially 64 ID.